2022
DOI: 10.3390/bios12050300
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Detection of the Receptor-Binding Domain of the SARS-CoV-2 Spike Glycoprotein at Physiologically Relevant Concentrations Using Surface-Enhanced Raman Spectroscopy

Abstract: Surface-enhanced Raman scattering (SERS) spectroscopy is a surface- or cavity-enhanced variant of Raman scattering spectroscopy that allows the detection of analytes with a sensitivity down to single molecules. This method involves the use of SERS-active surfaces or cavities capable of concentrating incident radiation into small mode volumes containing the analyte. Here, we have engineered an ultranarrow metal–dielectric nano-cavity out of a film of the receptor-binding domain (RBD) of SARS-CoV-2 spike (S) gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Many of the technologies described above were developed and designed to detect RBD to diagnose SARS-CoV-2. For example, Raman spectroscopy, [390][391][392][393] electrochemical methods, [394][395][396] localized surface plasmon resonance (LSPR) 397 and lateral ow tomography. 333,398 Recently, Yang et al reported a high-affinity SARS-CoV-2 Omicron variant RBD-binding aptamer (SCORe) that binds to the Omicron BA.1 and BA.2 variant RBD with affinity at the nM level.…”
Section: Sars-cov-2 Sp Detectionmentioning
confidence: 99%
“…Many of the technologies described above were developed and designed to detect RBD to diagnose SARS-CoV-2. For example, Raman spectroscopy, [390][391][392][393] electrochemical methods, [394][395][396] localized surface plasmon resonance (LSPR) 397 and lateral ow tomography. 333,398 Recently, Yang et al reported a high-affinity SARS-CoV-2 Omicron variant RBD-binding aptamer (SCORe) that binds to the Omicron BA.1 and BA.2 variant RBD with affinity at the nM level.…”
Section: Sars-cov-2 Sp Detectionmentioning
confidence: 99%
“…However, such procedures cannot be used in the POC testing setup. Comparatively, SERS can provide quantitative data with excellent specificity, sensitivity, and multiplex detection capacity, and has previously been employed for POC settings [ 128 ].…”
Section: Sers Based Diagnosis Of Virusmentioning
confidence: 99%
“…Several groups have demonstrated the achievement of strong electric fields thanks to plasmonic nanoparticles/nanostructures deposited on a metallic film serving as a mirror [10][11][12][13][14][15][16]. Furthermore, a great number of research groups have studied the coupling of plasmonic nanoparticles with nanogaps or subnanogaps [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. These various groups have theoretically and experimentally investigated great enhancements of the electromagnetic field concerning the coupling of these plasmonic nanoparticles with nanogaps (or subnanogaps) [35][36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…A strong motivation for the investigation of gap plasmons is the effect of surface-enhanced Raman scattering (SERS), which relies on plasmonic enhancement to enable the identification of trace molecules captured within gaps [54]. SERS is extremely important for medical diagnostics, for instance for cancer detection, imaging, and therapy, drug delivery, and the quantitative control of biomarkers, including glycated proteins and cardiovascular biomarkers, and viruses [34,[55][56][57][58][59]. For instance, Sarychev et al demonstrated a sensitive detection of less than 1 pg of a biological molecule (the spike glycoprotein of SARS-CoV-2) by employing a nanometric cavity formed by an Ag film and a layer of a receptor-binding domain of this glycoprotein [34].…”
Section: Introductionmentioning
confidence: 99%